Conservative management of kienbock's disease in a 24 year old adult : A case report - Shetty, Sanath Kumar; Ballal, Aditya; Rai, H. Ravindranath (Journal of Health and Allied Sciences NU, 2015)
Kienbock's disease also known as Lunatomalacia is a rare disorder involving the lunate. Damage to the lunate can lead to pain, stiffness, and in late stages, arthritis of the wrist. This disease is most common in men between the ages of 20 and 40 and rarely affects both wrists. Here we present a 35 year old male manual labourer who presented to our department with complaints of progressive pain and stiffness of his dominant wrist.Radiographically he was diagnosed to have Lichtmann class IIIA Kienbock's disease of the left wrist. He was managed with analgesics and wrist physiotherapy. On a review at three months he had an acceptable range of motion of the wrist he was symptom free.This article presents our patients history, radiological findings and management.
Keywords: Lunatomalacia; avascular necrosis; Kienbock